Bio-Based Jet Fuel Production by Transesterification of Nettle Seeds - Gurkan Aydin, Sinem; Ozgen, Arzu (Engineering, Technology & Applied Science Research, 2023)
The use of petroleum-based fuels in air transport and the increase in oil prices over the years have increased fuel costs. Due to this increase, fuel manufacturers and airline companies have started to search for alternative fuels. Since aviation has an important place in the transportation sector, biomass has the greatest potential in the search for renewable energy sources. Biological substances of plant and animal origin and containing carbon compounds are energy sources, and the fuels produced from them are called biofuels. Biofuels are an important source of sustainable energy, which greatly reduces the greenhouse gas effect, improves weather conditions, reduces dependence on oil produced from fossil fuels, and is important for new markets. The nettle seed oil used in the current study was purchased from the local market and was obtained using the cold-pressing method at low temperatures. After the completion of the transesterification process, a two-phase mixture consisting of biofuel-glycerin was obtained, and the upper phase containing fatty acids was taken and transferred to a clean tube. After the final washing processes, bio jet fuel was obtained by adding chemicals at certain rates. The analysis of the obtained fuel was conducted at the Tubitak Marmara Research Centre. When the report was evaluated and compared with international standards, consistent results were obtained. It can be predicted that sustainable fuels can replace fossil fuels in the future.